Dysregulation of AKT1, a miR‐138 target gene, is involved in the migration and invasion of tongue squamous cell carcinoma. (11th February 2017) - Ji, Muyuan; Wang, Wei; Yan, Wangxiang; Chen, Dan; Ding, Xueqiang; Wang, Anxun
Abstract : Background: AKT1, also known as PKBα, is abnormally expressed in various malignancies. In this study, we aimed to evaluate the role of AKT1 in the tongue squamous cell carcinoma (TSCC) and further clarify the mechanisms of AKT1 in the migration and invasion of TSCC. Methods: At first, immunohistochemistry (IHC) was conducted to detect the expression of AKT1 in TSCC. Then, we determined the role of AKT1 in the migration and invasion of TSCC and further investigated whether AKT1 was the target gene of miR‐138 using dual luciferase reporter assays and Western blot. Results: Immunohistochemistry results suggested that AKT1 dysregulation was a frequent event in TSCC, and upregulation of AKT1 was correlated with lymph node metastasis and associated with reduced overall survival. UM1 cells with higher migratory and invasive abilities had more robust AKT1 protein expression than UM2 cells with lower migratory and invasive abilities. The migration and invasion abilities were inhibited in UM1 cells upon AKT1 knockdown, meanwhile resulted in a decline of metastasis‐related proteins (vimentin, slug, and pERK1/2), and upregulation of E‐cadherin. Luciferase assays revealed that AKT1 was directly targeted by miR‐138, and ectopic transfection of miR‐138 reduced the expression of AKT1 protein. Conclusions: Our results confirm that upregulation of AKT1, a miR‐138 target gene, is a frequent event in TSCC and contributes to the aggressive behaviors and poor prognosis of TSCC.